2001
DOI: 10.4049/jimmunol.166.4.2651
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Induced IL-18 Secretion from Murine Kupffer Cells Independently of Myeloid Differentiation Factor 88 That Is Critically Involved in Induction of Production of IL-12 and IL-1β

Abstract: IL-18, produced as biologically inactive precursor, is secreted from LPS-stimulated macrophages after cleavage by caspase-1. In this study, we investigated the mechanism underlying caspase-1-mediated IL-18 secretion. Kupffer cells constantly stored IL-18 and constitutively expressed caspase-1. Inhibition of new protein synthesis only slightly reduced IL-18 secretion, while it decreased and abrogated their IL-1β and IL-12 secretion, respectively. Kupffer cells deficient in Toll-like receptor (TLR) 4, an LPS-sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
183
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 224 publications
(192 citation statements)
references
References 44 publications
9
183
0
Order By: Relevance
“…As previously reported, pro-IL-18 is stored in Kupffer cells, 22 and IL-18 requires cleavage for its secretion by appropriate enzymes that are distinct depending on the sorts of stimuli. 7,8,11 The molecular basis of the processing of IL-18 is still unknown.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…As previously reported, pro-IL-18 is stored in Kupffer cells, 22 and IL-18 requires cleavage for its secretion by appropriate enzymes that are distinct depending on the sorts of stimuli. 7,8,11 The molecular basis of the processing of IL-18 is still unknown.…”
mentioning
confidence: 61%
“…A recent study demonstrated that upon stimulation with LPS, caspase-1 is activated via Toll-like receptor (TLR)-4, a signaling receptor for LPS, but independently of myeloid differentiation factor-88, an adaptor molecule for TLR-mediated signaling, leading to IL-18 secretion. 22 However, we do not yet know the signaling pathway after TLR-4 activation. This is also the case for FasL-induced IL-18 secretion.…”
mentioning
confidence: 99%
“…Whether this is unique to LM, to other cytoplasmic intracellular pathogens, or is a more general property of infection vs immunization is uncertain. Perhaps this is the same pathway that accounts for MyD88-independent production of IL-18 observed following LM infection in mice (20), and production of IFN-␤ in macrophages when LM gains access to the cytoplasm (21,22). It is tantalizing to hypothesize that the key difference in induction of specific immunity between LM infection and the administration of soluble Ag lies in the ability of LM to gain access to the intracytoplasmic cellular compartment, and thereby activate classes of Ag sensing molecules unique to this compartment.…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, Kupffer cells express TLR4 and are responsive to LPS [18]. Upon triggering, TLR4 signaling drives Kupffer cells to produce TNF-a, IL-1b, IL-6, IL-12, IL-18, and antiinflammatory cytokine IL-10 [19].…”
Section: Tlr4 Expression In the Livermentioning
confidence: 99%